(untitled) (International Journal of Physiotherapy, 2016)
Background: Osteoporosis is a metabolic bone disease that progress silently leading to loss of bone mass. The fractures caused because of osteoporotic bones are widely prevalent in India and are one of the common causes of morbidity and mortality in elderly population. The Health care providers and Physiotherapist have a specific role in osteoporosis through exercise prescription, education and strategies to maximize function, reduce the risk of falls and manage pain. There are various treatment protocols involved treatment and prevention of osteoporosis, among which the exercises have an impact on the bone mineral density. The studies have presented the importance of exercises in improving the bone mass apart from improving function and reducing the risk of fractures. The various type and intensity of exercises vary with age and it is important to understand the benefits and adverse effects. There are few studies emphasizing on the regimes and type and intensity of exercises. This manuscript provides an overview of physiotherapy management for bone health with an emphasis on the clinical recommendations and exercise prescription. The effects of exercise and its evidence in prevention and treatment of osteoporosis are also discussed. Methods: The article was framed with the Data sourced from electronic database, systematic reviews, meta-analyses from pub med, Medline, science direct and Cochrane library. Result: Early intervention and exercise has a positive correlation against BMD and bone health. Conclusion: Various exercises have their benefits in osteoporosis and a combination of exercises must be recommended based on a methodical assessment.